2006
DOI: 10.1021/es0611801
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Nitrous Oxide Emission from Pig Manure Composting by Addition of Nitrite-Oxidizing Bacteria

Abstract: Nitrous oxide (N2O) is emitted from pig manure composting, and the emission correlates with nitrite (NO2-) accumulation in the composting material. In the present study, we added nitrite-oxidizing bacteria (NOB)to inhibit NO2- accumulation and evaluated its effect on N2O emission in a laboratory-scale composting experiment. Mature pig manure compost (MPMC) containing NOB at 10(6) MPN g(-1) WM or cultured MPMC (cul-MPMC) NOB at 10(11) MPN g(-1) WM was added after the thermophilic phase of composting. The additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…It can be speculated that this environment is also conducive to N 2 O emissions via nitrifier denitrification if NO 2 2 accumulates because of selective inhibition of NOB (de Boer and Kowalchuk, 2001;Kool et al, 2011). Indeed, Fukumoto (2006) showed that addition of NOB to a compost prevented NO 2 2 accumulation and N 2 O emission.…”
Section: Ch 4 and N 2 O Emissions From Manure: Sources And Sinksmentioning
confidence: 99%
“…It can be speculated that this environment is also conducive to N 2 O emissions via nitrifier denitrification if NO 2 2 accumulates because of selective inhibition of NOB (de Boer and Kowalchuk, 2001;Kool et al, 2011). Indeed, Fukumoto (2006) showed that addition of NOB to a compost prevented NO 2 2 accumulation and N 2 O emission.…”
Section: Ch 4 and N 2 O Emissions From Manure: Sources And Sinksmentioning
confidence: 99%
“…First, there was a difference in the scale of piled manure compared to that of the previous study (Fukumoto et al 2006). In the case of piled compost, the volume of the anaerobic portions established inside the pile may increase logarithmically compared to the volume of aerobic portions as the scale of the compost pile increases.…”
Section: Discussionmentioning
confidence: 74%
“…At the practical scale employed in the present trials, N2O mitigation reached 11% in Run 1, but conversely increased to 38% in Run 2. In following the procedure previously reported by Fukumoto et al (2006), mature compost was added at the 6-week turning since N2O generation had started in both runs. Figure 3 shows the changes in daily N2O emissions and BOD degradation during composting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations